Transneuronal Propagation of Pathologic α-Synuclein from the Gut to the Brain Models Parkinson's Disease - Kim, Sangjune; Kwon, Seung-Hwan; Kam, Tae-In; Panicker, Nikhil; Karuppagounder, Senthilkumar S; Lee, Saebom; Lee, Jun Hee; Kim, Wonjoong Richard; Kook, Minjee; Foss, Catherine A; Shen, Chentian; Lee, Hojae; et al. (Neuron (Cambridge, Mass.), 2019)
Analysis of human pathology led Braak to postulate that α-synuclein (α-syn) pathology could spread from the gut to brain via the vagus nerve. Here, we test this postulate by assessing α-synucleinopathy in the brain in a novel gut-to-brain α-syn transmission mouse model, where pathological α-syn preformed fibrils were injected into the duodenal and pyloric muscularis layer. Spread of pathologic α-syn in brain, as assessed by phosphorylation of serine 129 of α-syn, was observed first in the dorsal motor nucleus, then in caudal portions of the hindbrain, including the locus coeruleus, and much later in basolateral amygdala, dorsal raphe nucleus, and the substantia nigra pars compacta. Moreover, loss of dopaminergic neurons and motor and non-motor symptoms were observed in a similar temporal manner. Truncal vagotomy and α-syn deficiency prevented the gut-to-brain spread of α-synucleinopathy and associated neurodegeneration and behavioral deficits. This study supports the Braak hypothesis in the etiology of idiopathic Parkinson's disease (PD).